1986
DOI: 10.1111/j.1476-5381.1986.tb10155.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of prostanoid relaxant/inhibitory receptors (ψ) using a highly selective agonist, TR4979

Abstract: 3 On other respiratory tissues known to contain mixtures of the 'X1,2,3'-and 'j'-receptors (guinea-pig trachea and lung strip, cat lung strip and human bronchial muscle), TR4979 consistently acted as a potent relaxant whereas PGE2 and to a lesser extent PGE1 had significant contractant activities. 4 Human pregnant uterus, guinea-pig and rat pseudo-pregnant uteri, rat colon and fundic strips and chick ileum are known to contain one or more of the three subclasses of the 'X'-receptor. TR4979 (l09-10-5M) was inac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
78
2

Year Published

1991
1991
2011
2011

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 137 publications
(85 citation statements)
references
References 20 publications
5
78
2
Order By: Relevance
“…The chick ileum finding is surprising, since Gardiner (1986) reported that butaprost was inactive on this preparation over a wide concentration range (2 nM-200 g.M). In Gardiner's experiments the chick ileum was simultaneously exposed to several receptor antagonists (hyoscine, mepyramine, phenoxybenzamine, propranolol, methysergide) and the cyclo-oxygenase inhibitor indomethacin.…”
Section: Discussionmentioning
confidence: 56%
See 2 more Smart Citations
“…The chick ileum finding is surprising, since Gardiner (1986) reported that butaprost was inactive on this preparation over a wide concentration range (2 nM-200 g.M). In Gardiner's experiments the chick ileum was simultaneously exposed to several receptor antagonists (hyoscine, mepyramine, phenoxybenzamine, propranolol, methysergide) and the cyclo-oxygenase inhibitor indomethacin.…”
Section: Discussionmentioning
confidence: 56%
“…1, mepyramine 0. 1, phenoxybenzamine 0.1, propranolol 3, methysergide 0.2 gxg ml-' and indomethacin 3 fiM) used by Gardiner (1986) had no effect on the log concentration-response curves of either PGE2 or butaprost.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The selective EP2-receptor agonists, 1 1-deoxy PGEI (Lawrence et al, 1992), butaprost (Gardiner, 1986) and AH 13205 (Nials et al, 1993) also inhibited chemotaxis, giving maximal inhibitions of 43.8 +7.9% (n=3), 65.2±6.2% (n=5) and 61.9 ± 2.7% (n = 3), respectively at concentrations of 1OyM (Figure 2a). Taking the maximal effect of PGE2 at 10 $M as 100% response, apparent EC5&s of 106.4±63 nM, 140.9±64.7 nM and 1.58±0.73 pM were determined for butaprost, 1 1-deoxy PGEI and AH 13205, respectively.…”
Section: Inhibition Of Chemotaxis By Selective Ep Agonistsmentioning
confidence: 99%
“…In general, conclusions must be drawn on the basis of results obtained from various combinations of receptor selective compounds, and a process of elimination. To date, butaprost (TR4979) (Gardiner et al, 1986) appears to be the most selective agonist for the study of EP-receptors in that it shows high potency and selectivity at the EP2-receptor subtype, with little or no activity for the EP1-or EP3-receptors. Other PGE analogues such as sulprostone, rioprostil and misoprostol are useful but show activity at two EP-receptor types.…”
Section: Introductionmentioning
confidence: 99%